Talk on television : audience participation and public debate - Livingstone, Sonia M.; Lunt, Peter K. (Peter Kenneth), 1956- (London ; New York : Routledge, 1994)
Not only is everyday conversation increasingly dependent on television, but more and more people are appearing on television to discuss social and personal issues. Is any public good served by these programmes or are they simply trashy entertainment which fills the schedules cheaply? Talk on Television examines the value and significance of televised public debate. Analysing a wide range of programmes including Kilroy, Donohue and The Oprah Winfrey Show, the authors draw on interviews with both the studio participants and with those watching at home. They ask how the media manage discussion programmes and whether the programmes really are providing new 'spaces' for public participators. They find out how audiences interpret the programmes when they appear on the screen themselves, and they unravel the conventions - debate, romance, therapy - which make up the genre. They also consider TV's function as a medium of education and information, finally discussing the dangers and opportunities the genre holds for audience participation and public debate in the future.[publisher].
Chapter 1 Television talk and talking about television -- chapter 2 The mass media, democracy and the public sphere -- chapter 3 Studio debates and audience discussions -- A television genre -- chapter 4 The critical viewer -- chapter 5 Media constructions of expertise and common sense -- chapter 6 Media management of argument and rhetoric -- chapter 7 Studio discussions, social spaces and postmodernity.
Includes bibliographical references (pages 186-197) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Television talk shows; Television viewers; Television broadcasting -- Social aspects; Audience participation television programs; Television viewers; Television broadcasting -- social aspects; Talk-shows.; Téléspectateurs.; Télévision -- Aspect social; Émissions télévisées à participation du public; viewers (observers); PERFORMING ARTS -- Television -- Reference; Television broadcasting -- Social aspects; Television talk shows; Television viewers; Fernsehen; Publikum; Talkshow; Debatten; Televisie; Publiek; TV-publik -- Storbritannien; TV-publik -- Förenta staterna; Politics -- Role of -- Television; Electronic books; Television talk shows; Television talk shows